Fuzzy AHP and its application to sustainable energy planning decision problem / Liana Najib and Lazim Abdullah - Najib, Liana; Abdullah, Lazim (2021)
The uncertainty during the decision-making process lead to difficulty in understanding the situation of the problems occurs. However, there are lots of mathematical tools that described the multiplicity, complexity and sensitivity of the human thoughts in the decision process todays. To deal with uncertainties of information, the fuzzy set theory is introduced. Thus, the aim of the paper is to evaluate the alternatives selection with respect to sustainable energy planning problems using fuzzy multi criteria decision-making. In this paper, the fuzzy analytic hierarchy process is applied to conduct the relative weights priority of energy planning selection. The study suggests that Combined Heat and Power (CHP) system is recommended for the sustainable energy planning decision compared to other options of energy.